2020
DOI: 10.1371/journal.pone.0232250
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitating factors in the prevention of diabetes type 2 and gestational diabetes in vulnerable groups: A scoping review

Abstract: Type 2 diabetes mellitus (T2DM) and gestational diabetes (GDM) are globally on the rise, accompanied by comorbidities and associated health costs. Increased physical activity, healthy nutrition, and weight loss have shown the potential to prevent T2DM/GDM. Despite this, reaching vulnerable groups remains a key challenge. The aim of this scoping review was to identify barriers and facilitating factors in the prevention of T2DM/GDM in vulnerable groups. Methods We conducted a systematic literature search in May … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
3
0
1
Order By: Relevance
“…This scoping review adds a detailed list of communication strategies in the prevention of type 2 diabetes and gestational diabetes in vulnerable groups to the literature. In conjunction with recently described barriers and facilitating factors in diabetes prevention in vulnerable groups [ 50 ]; therefore, future preventive programs can benefit from these findings or already existing programs could be adapted.…”
Section: Discussionmentioning
confidence: 97%
“…This scoping review adds a detailed list of communication strategies in the prevention of type 2 diabetes and gestational diabetes in vulnerable groups to the literature. In conjunction with recently described barriers and facilitating factors in diabetes prevention in vulnerable groups [ 50 ]; therefore, future preventive programs can benefit from these findings or already existing programs could be adapted.…”
Section: Discussionmentioning
confidence: 97%
“…Other studies have found that previous difficult life experiences may increase the risk for allostatic load [ 15 ] and unhealthy habits later in life [ 13 , 14 ], as well as being barriers for establishing healthy habits [ 9 11 ]. Life experiences in childhood and young life influence grow of SOC in adult life [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is emphasized that individuals trying to change health habits may meet different barriers [ 9 11 ]. The barriers might include negative experiences from childhood, social life experiences [ 12 ] and family/work situation [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Los factores económicos, como el costo para el acceso a programas preventivos y alimentos saludables, así como las interacciones familiares, laborales y sociales, pueden facilitar o dificultar la prevención de la enfermedad (Breuing et al, 2020). La prevención del estrés relacionado con la diabetes -entendido como el estrés resultante del ajuste psicosocial del individuo para satisfacer los requerimientos del tratamiento para la diabetes-se centra en la mejora de la comunicación médico-paciente y el apoyo emocional a través de intervenciones individuales y grupales (Skinner et al, 2019).…”
Section: Prevención De Problemas Psicológicos Asociados a La Dmunclassified